2000
DOI: 10.1590/s0100-204x2000001200023
|View full text |Cite
|
Sign up to set email alerts
|

Restrição alimentar e atividade ovariana luteal cíclica pós-parto em vacas girolanda

Abstract: RESUMO -Objetivou-se neste trabalho verificar se a restrição alimentar no pós-parto em vacas Girolanda, multíparas, de bom escore de condição corporal (ECC = 3,5 a 4,5) ao parto será suficiente para impedir o reinício da atividade ovariana luteal cíclica (AOLC) pós-parto. Os animais foram distribuídos em três tratamentos: Grupo I (n = 15), mantença; Grupo II (n = 10) e Grupo III (n = 13), sendo que os grupos II e III receberam restrição alimentar até 90 e 180 dias pós-parto, respectivamente. As pesagens e aval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 15 publications
(12 reference statements)
0
6
0
4
Order By: Relevance
“…According to Ferreira et al (2000), monitoring postpartum body weight in lactating cows is fundamental to ensure that body reserves will be adequate for cows to exhibit estrus and guarantee pregnancy. Furthermore, the authors reported that a BCS of 3.5 is ideal for cows to show estrus within 90 days postpartum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Ferreira et al (2000), monitoring postpartum body weight in lactating cows is fundamental to ensure that body reserves will be adequate for cows to exhibit estrus and guarantee pregnancy. Furthermore, the authors reported that a BCS of 3.5 is ideal for cows to show estrus within 90 days postpartum.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the average BCS of 3.77 indicates that cows had sufficient energy reserves during lactation, which is a positive characteristic of F1 Holstein x Zebu cows. Ferreira et al (2000) reported that the desirable BCS in late lactation, close to the dry period of the cow, should be approximately 3.5, while at calving it should be 3.5 to 4.0. This assessment in late lactation is essential to prevent some cows from becoming too thin at drying off.…”
Section: Discussionmentioning
confidence: 99%
“…Gross et al (2011) verified that the feed restriction of lactating cows for three weeks reduced their body weight. Ferreira et al (2000) stated that the monitoring of postpartum BW of lactating cows is fundamental so that they have sufficient reserves for the manifestation of estrus and guarantee of pregnancy. The same authors evaluated Girolando cows under conditions of feed restriction and concluded that the weight loss of 15.2% in the early lactation did not affect reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the mean value for BCS was 3.6 in the final third of lactation, even with the restriction of the diet supply, indicating that animals had sufficient energy reserves for the postpartum period. Ferreira et al (2000) reported that the desirable BCS in the final third of lactation, close to the drying time of the cow, is close to 3.5, whereas at the time of delivery it is 3.5 to 4.0. This evaluation in the final third of lactation is important to prevent some cows from getting too thin in the drying period, so there is no time to recover the necessary reserves during the dry period, aiming to reach a good body condition (Smith et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation